Influence of the Koran on Middle Ages Literary Monuments - Kurmangali Г.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The article emphasizes the importance of medieval poetry in the history of Kazakh literature, as well as the ideological and artistic significance of Turkic literature. It analyzes such topics as the state of affairs of the era, moral problems, changing morals which became the basis in the works of the medieval period. In particular, the influence of the Koran on the works of the medieval period is widely discussed. The main idea of the works of the medieval period was to explain the religion of Islam to the people and call them to spiritual purity. Islam influenced the development of medieval literature in Turkic literature, and it can be seen from the use of the Qur’an and the hadith of the Prophet in the writings of that era. The article reveals how medieval poets sang didactic problems, which were the main theme of the works of the Karakhan Era and their contribution to the development of Turkic literature. The article reveals how medieval poets sang didactic problems, which were the main theme of the works of the Karakhan era and their contribution to the development of Turkic literature.